Advanced analytical techniques in fatigue and rutting related characterisations of modified bitumen: literature review - Subhy, Ayad (Elsevier, 2017)
Fatigue and rutting are the two major failure distresses in flexible pavement that affect significantly the serviceability of pavement. The properties of bitumen have a direct effect on controlling the fatigue and rutting distresses. Because of the increase in vehicular loading and repetitions, the modification of neat bitumens becomes a widespread practice to improve their mechanical properties. Any improvements obtained from developing modified binders need be reflected by fundamental testing parameters. The empirical testing methods and Superpave grading procedure that were developed mainly for unmodified bitumens have failed in many cases to predict the performance of modified bitumens. Evaluation the influence of such modifiers needs be based on characterising accurately the inherent resistance of binders to fatigue and rutting damage. The most advanced tests and fundamental analysis methods for characterising the fatigue and rutting properties of binders, are discussed and presented in this paper. These include fatigue and ductile fracture evaluation of binders using time sweep and double-edged notched tension (DENT) tests. For bitumen rutting evaluation, the SHRP rutting parameter, Shenoy rutting parameter, ZSV and MSCR are discussed. The dynamic shear rheometer (DSR) has been largely used to characterise fundamentally the viscoelastic properties of bitumens. A detailed description of the main elements associated with the DSR and Dynamic Mechanical Analysis (DMA) are also presented in this paper.